My Exposure to Violence (MY ETV): tradução e adaptação transcultural para o português brasileiro - Carvalho, Marcos Clint Leal de (2021)
Exposure to community violence (CVE) has been associated with several adverse outcomes in adolescents. No instrument for measuring CVE in adolescents that had undergone a rigorous process of translation and cross-cultural adaptation was found in Portuguese. Thus, this study proposed to translate and adapt the CVE measurement instrument My Exposure to Violence (My ETV) into Brazilian Portuguese. This is a methodological study. The translation and cross-cultural adaptation process consisted of seven steps: (I) initial translations, (II) synthesis of translations, (III) back-translations, (IV) cross-cultural pre-adaptation, (V) evaluation by a committee of judges, (VI) pre-test and (VII) submission to the original authors. Eight judges participated in stage V, each one fitting into at least one of the following areas of expertise: violence, methodology and linguistics. They evaluated the My ETV in relation to semantic, idiomatic, cultural, and conceptual equivalences. Validity Index for each item (CVI-I) and for the instrument mean (CVI-M) were calculated. The pre-test was carried out with 39 adolescents aged 15 to 19 years, enrolled in a federal educational institution in Fortaleza – Ceará, using the Survey Monkey® online survey tool. The study was approved by the Research Ethics Committees of UFC and IFCE (report numbers 4.026.654 e 4.328.491, respectively). In step I, two translations were produced, T-1 and T-2. The few differences between the two were resolved in step II through discussion between the translators, mediated by an external observer, generating the synthesis version of the translations (T-12), which was translated back to English independently by two English mother-tongue professional translators. In step IV, the synthesis version T12 was revised, with specific linguistic changes being carried out to facilitate understanding by the target audience. In step V, two items (21 and 22) had a CVI ≤ 0.78 and would necessarily need to be revised, however, due to the high relevance of the judges' suggestions, 19 of the 23 items (82.60%) underwent some modification. The instrument's CVI-M was 0.92. In stage VI, the mean age of the 39 participants in the pre-test was 17.48 years (± 1.27). Most were female (51.28%) and lived in Fortaleza (74.36%). Students from all shifts (morning, afternoon, and evening) from all high school grades and university students participated; most attended the third year of high school (48.72%) and the morning shift (43.59%). The pre-final version of the instrument had 21 of the 23 items (91.30%) fully understood by more than 90% of the participants. No changes were made to the final version of the instrument. My Exposure to Violence (My ETV) was cross-culturally adapted into Portuguese and was well understood by the target population. Further study will assess its psychometric properties.